Falling in Old Age in Samsun: 2010-2015 - Kılınç, Ömer; Polat, Salih Tunahan; Turla, Ahmet; Aydın, Berna (The Bulletin of Legal Medicine, 2017)
Objective: The purpose of this study is to evaluate cases over the age of 65 who are admitted for falling and to lead the way for the measures to be taken to minimize the harm.Materials and Methods: 489 patients at and over the age of 65 who were admitted to Ondokuz Mayıs University Health Application and Research Center due to falling between the dates of 01.08.2010 and 31.07.2015 were included in the study.Forensic files and hospital automation system data of the cases were analyzed and their genders, ages, time of admission, type of fall, wound areas, fractured bones, presence of comorbid disease, the department in which they were treated and their treatment status were examined retrospectively. The data obtained from this cross- sectional study were assessed with SPSS 15.0 program.Results: 230 (47,0%) of the cases were men, while 259 (53,0%) were women. The cases were mostly admitted in July (12.3%), on Sundays (15.7%) and between 16.00 and 23.59 (46.6%). The most frequent place of fall was inside the house (43,3%). Internal organ injury was seen in 16,4% of the patients while bone fracture was seen in 53,2%. Most frequently fractured bone was the femur (41,5%).Conclusion: Injuries associated with falling due to the increase in old population creates an important social problem. Falling is not an inevitable result of old age. Preventing falls in old age will decrease the dependency about daily life activities, increase life quality and decrease health care costs.
Keywords: Old Age; Falling; Femur Fracture